Fair exotics : xenophobic subjects in English literature, 1720-1850 - Sudan, Rajani (New cultural studies., 2002)
"An original and elegant work that will make signal contributions to the fields of eighteenth-century studies and Romanticism, and to the study of British nationalism and colonialism."--Adela Pinch, University of Michigan.